Prevention of acute and chronic allograft rejection with CD4+CD25+Foxp3+ regulatory T lymphocytes - Joffre, Olivier (Nature Publishing Company, 2008)
One of the major challenges in transplantation medicine is to control the very strong immune-responses to foreign antigens responsible for graft-rejection. Whereas immunosuppressive drugs efficiently inhibit acute graft rejection, a non-diminishing proportion of patients suffers from chronic rejection which ultimately leads to functional loss of the graft1. Induction of immunological tolerance to transplants would avoid rejection and the need for lifelong treatment with immunosuppressive drugs1,2. Tolerance to self-antigens is ensured naturally by several mechanisms3, one of the major ones relying on the activity of regulatory T lymphocytes4,5. Here we show that in mice treated with clinically acceptable levels of irradiation, regulatory CD4(+)CD25(+)Foxp3(+) T cells stimulated in vitro with alloantigens induced long-term tolerance to bone marrow and subsequent skin and cardiac allografts. Regulatory T cells specific for directly presented donor antigens prevented only acute rejection, despite hematopoietic chimerism. On the other hand, regulatory T cells specific for directly and indirectly presented alloantigens prevented both acute and chronic rejection. Our findings demonstrate the potential of appropriately stimulated regulatory T cells for future cell-based therapeutic approaches to induce lifelong immunological tolerance to allogeneic transplants.